Single-cell profiling reveals immune disturbances landscape and HLA-F-mediated immune tolerance at the maternal-fetal interface in preeclampsia - Luo, Fangyuan; Liu, Fulin; Guo, Yingzhe; Xu, Wenming; Li, Yilin; Yi, Jun; Fournier, Thierry; Degrelle, Séverine; Zitouni, Hedia; Hernandez, Isabelle; Liu, Xinghui; Huang, Yu; et al. (Frontiers in Immunology, 2023)
Normally functioning immune cells play an important role in the establishment of immune tolerance at the maternal-fetal interface (MFI) and the maintenance of normal pregnancy, while dysfunction in immune cells is associated with pathologies of pregnancy such as preeclampsia (PE). Through single-cell RNA sequencing (scRNAseq) on placental decidua, disease-related IGFBP1 + SPP1 + extracellular villus trophoblast (EVT) was identified in the preeclamptic placental decidual tissue, accompanied by newly discovered immune cellular dysfunction such as reduced ribosomal functions of NK populations and abnormal expression of human leukocyte antigens (HLA) molecules in most cell clusters. The reduced expression pattern of HLA-F in PE samples was validated using immunofluorescence, suggesting that HLA-F may be involved in facilitating maternal immune tolerance. Over-expression of HLA-F in Jar cells promoted cell proliferation, invasion, and migration while underexpression had the opposite effect. In NK-92MI cells, over-expression of HLA-F increased the secretion of cytokines such as CSF1 and CCL22, which function as promoters of MFI immune tolerance. Our findings regarding cellular heterogeneity and immune cellular dysfunction, as revealed by scRNA-seq, and the function of HLA-F in cells provide new perspectives for further investigation of their roles in the pathogenesis of preeclampsia.